HYDROGEOLOGICAL ASSESSMENT OF GROUNDWATER DEGRADATION AT THE EASTERN NESTOS RIVER DELTA, N.E. GREECE. - Gkiougkis, I.; Mwila, G.; Pliakas, F.; Kallioras, A.; Diamantis, I. (Bulletin of the Geological Society of Greece, 2010)
This paper deals with the hydrogeological study of the evolution of groundwater salinisation - degradation at the eastern Nestos River Delta. Relevant field works including in-situ measurements of groundwater level, pH, Specific Electrical Conductivity (SEC) and temperature took place in the years 2008 and 2009. Groundwater samples were also collected for chemical analysis at the Engineering Geology Laboratory of the Department of Civil Engineering of D.U.Th. (July of 2009). Important conclusions regarding the progress of the groundwater degradation at the study area were drawn based on the analysis of all the available data and the elaboration of the designed piezometric maps and the various maps showing the distribution of SEC, Chloride, SAR (Sodium Absorption Ratio) and Revelle coefficient values. Some managerial suggestions for the confrontation of the seawater intrusion regime of the study area are also included.